Why Bystander act or do not act Prosocially in Bullying Situations - Triani Arfah; Istiana Tajuddin; Desi Ariani (Har Press Indonesia, 2024)
Individuals, as bystanders, can reduce bullying by engaging in prosocial behavior toward victims. However, many students either side with the perpetrator or passively observe. This study aims to explore the factors influencing prosocial bystander behavior in bullying situations among students at 'X' Maros Junior High School. Using a mixed-method approach (quantitative and qualitative), the study involved 263 students aged 12–15 years who had witnessed bullying. Instruments used included a prosocial behavior questionnaire, a vignette, and open-ended questions. The findings revealed that most bystanders in Maros Junior High School were actively engaged in all stages of prosocial behavior, including stopping the perpetrator, reporting to a teacher, and offering social support to the victim. The factors influencing prosocial behavior were both personal/psychological and situational. Personal factors included attitudes toward bullying, empathy, emotional involvement, risk perception, religiosity, victim attribution, self-efficacy, and conformity. Situational factors included the relationship with the perpetrator or victim, the presence of other bystanders, and the severity of the bullying. Moreover, the study highlights the importance of promoting empathy and emotional involvement as key factors in encouraging bystanders to act. The presence of peers also plays a critical role in influencing whether bystanders intervene. These findings offer valuable insights for developing strategies to encourage adolescents to intervene and support peers who are victims of bullying. The research contributes to the creation of effective anti-bullying programs by emphasizing the role of both personal and situational factors in shaping prosocial bystander behavior.